(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate, through microscopic analysis, the repair of critical defects in rabbit calvaria after the use of particulate autogenous bone or particulate autogenous bone associated with inorganic biomaterial. Six male albino rabbits, New Zealand, were used, in which 4 defects were performed in each calvaria and randomly divided into 4 equitable groups: Group I – performed bone defect; Group II – performed bone defect and filled with particulate autogenous bone; Group III – performed bone defect and filled with particulate inorganic material (Bio-Oss®, Geistlich from Brazil); Group IV – performed bone defect and filled with particulate autogenous bone associated with particulate inorganic material (Bio-Oss® - Geistlich from Brazil) with proportion being 20:80. The analyze time of the procedure was 60 days. The microscopic analyze allowed to conclude that the autogenous, the Bio-Oss® and the Bio-Oss® associated with autogenous bone groups showed a bone neoformation on the defects, characterizing the material osteoconductive. However, the complete defect closure occurred on the autogenous bone and the autogenous bone associated with the inorganic bone, showing that the presence of the autogenous bone improves the characteristics of the biomaterial. The use of inorganic bone associated with the autogenous bone allowed a complete bone neoformation of the critic defect in the calvaria of rabbits.